A 3D 12‐Ring Zeolite with Ordered 4‐Ring Vacancies Occupied by (H2O)2 Dimers. Issue 49 (24th October 2014) - Liang, Jie; Su, Jie; Wang, Yingxia; Chen, Yanping; Zou, Xiaodong; Liao, Fuhui; Lin, Jianhua; Sun, Junliang
Abstract A germanate zeolite, PKU‐14, with a three‐ dimensional large‐pore channel system was structurally characterized by a combination of high‐resolution powder X‐ray diffraction, rotation electron diffraction, NMR, and IR spectroscopy. Ordered Ge4O4 vacancies inside the [46.612] cages has been found in PKU‐14, in which a unique (H2O)2 dimer was located at the vacancies and played a structure‐directing role. It is the first time that water clusters are found to be templates for ordered framework vacancies.